Liver transplantation in the Nordic countries – An intention to treat and post-transplant analysis from The Nordic Liver Transplant Registry 1982–2013. (June 2015) - Fosby, Bjarte; Melum, Espen; Bjøro, Kristian; Bennet, William; Rasmussen, Allan; Andersen, Ina Marie; Castedal, Maria; Olausson, Michael; Wibeck, Christina; Gotlieb, Mette; Gjertsen, Henrik; Toivonen, Leena; et al.
Abstract Aim and background. The Nordic Liver Transplant Registry (NLTR) accounts for all liver transplants performed in the Nordic countries since the start of the transplant program in 1982. Due to short waiting times, donor liver allocation has been made without considerations of the model of end-stage liver disease (MELD) score. We aimed to summarize key outcome measures and developments for the activity up to December 2013. Materials and methods. The registry is integrated with the operational waiting-list and liver allocation system of Scandiatransplant (www.scandiatransplant.org) and accounted at the end of 2013 for 6019 patients out of whom 5198 were transplanted. Data for recipient and donor characteristics and relevant end-points retransplantation and death are manually curated on an annual basis to allow for statistical analysis and the annual report. Results. Primary sclerosing cholangitis, acute hepatic failure, alcoholic liver disease, primary biliary cirrhosis and hepatocellular carcinoma are the five most frequent diagnoses (accounting for 15.3%, 10.8%, 10.6%, 9.3% and 9.0% of all transplants, respectively). Median waiting time for non-urgent liver transplantation during the last 10-year period was 39 days. Outcome has improved over time, and for patients transplanted during 2004–2013, overall one-, five- and 10-year survival rates were 91%, 80% and 71%, respectively. In an intention-to-treat analysis, corresponding numbers during the same time period were 87%, 75% and 66%, respectively. Conclusion. The liver transplant program in the Nordic countries provides comparable outcomes to programs with a MELD-based donor liver allocation system. Unique features comprise the diagnostic spectrum, waiting times and the availability of an integrated waiting list and transplant registry (NLTR).